PEMBANGUNAN KESEHATAN LINGKUNGAN MELALUI PENGOLAHAN SAMPAH ORGANIK DAN ANORGANIK LIMBAH RUMAH TANGGA MENJADI PRODUK BERMANFAAT DI KELURAHAN GERES KECAMATAN LABUHAN HAJI - Rohadi, Rohadi; Saniwati, Saniwati; Farhan, Najwa A’yuni; Ardiansyah, Randy; Bungawan, Ahmad Muhammad; Agustin, Della Arditha Wira; Juniyantika, Vina Dwi; Hardiani, Febrika; Hunaida, Patlial; Hadlin, Muhammad Wahyu Janwar; Aldi, Muhammad Warid (Jurnal Wicara Desa, 2023)
Geres Village is one of the areas located in Labuhan Haji District, East Lombok. Garbage scattered in every ditch, poor environmental sanitation, and dusty and sandy soil types cause environmental problems in this kelurahan. Therefore, socialization and training are held regarding the processing of organic and inorganic waste from household waste. This aims to increase knowledge related to the processing of organic and non-organic waste from household waste, so that it can reduce the negative impact of environmental pollution as well as improve the economy of the Geres Village community. The results of these activities show that it can increase community knowledge regarding the processing of organic waste into compost and non-organic waste into products of economic value such as trash cans, key toys, and flower pots. With this socialization and training, it is hoped that any knowledge shared can be properly conveyed and applied.